Evaluating Micro-Crack Propagation in Concrete Under Freeze-Thaw Cycles Using a Multi-Frequency Ultrasonic Approach - Fartosy, Sabah H.; Kohees, Mithaq; Mohammed Ali, Zubaidah A.; Faleeh, Jinan M.; Hassan, Salah (Salehan Institute of Higher Education, 2026)
Concrete is a widely used construction material that degrades over time for various reasons, meaning an integrity assessment is necessary for concrete to ensure it performs as expected for design requirements. This research employs velocity and attenuation of ultrasonic wave propagation to evaluate the development of micro-cracking in a concrete medium subjected to freezing and thawing. Four concrete cylinder samples were cast from an air-entrained admixture with various percentages of aggregate. Conventional Ultrasonic Pulse Velocity (UPV) testing was performed with three pairs of transducers (54 kHz, 250 kHz, and 500 kHz) on the specimens undergoing temperature cycling. Two methods of comparative analysis evaluated the relationship between inherent characteristics of the propagated waves and the induced development of cracks in the specimens. Results from the comparative analyses indicate that transducer frequency plays an important role in the accuracy and specificity of non-destructive testing (NDT) assessments. 54 kHz provides a more generic assessment of macro-scale deterioration; however, higher frequencies, and specifically 500 kHz, provide a level of detail that renders optimal air-entrained percentages distinguishable and freeze-thaw tested concrete's internal cracking development discernible with greater certainty. These results strongly support NDT testing of concrete for durability considerations with advanced blends in cold exposure regions. Such varying frequencies allow concrete stakeholders to appreciate global trends in addition to localized damage attributes for effective assessments of material capability and service life predictions.